Evaluation and Transplantation of a SARS-CoV-2 Seropositive Kidney Candidate. (10th March 2021) - Graves, Maya C.; Mehta, Sapna A.; Lonze, Bonnie E.; Ali, Nicole M.
Abstract : The COVID-19 pandemic affected transplant center activity in areas with high number of cases such as New York City and prompted reevaluation of patients awaiting organ transplant diagnosed with SARS-CoV-2 infection. To resume safe transplantation at our center, we found it necessary to (1) identify transplant candidates with possible exposure to or history of COVID-19 infection, (2) outline a clinical and laboratory assessment to determine adequate clinical recovery from COVID-19 for transplantation, and (3) determine whether the possibility of perioperative COVID-19 transmission from the patient to staff would pose unacceptable risk. Here, we describe our center's approach to proceeding with transplantation in a SARS-CoV-2 seropositive living donor kidney transplant recipient and describe early posttransplant outcomes.